Analisis Rantai Pasok Penjualan Sepatu Sekolah Masa Pandemi Covid-19 dengan Metode Weighted Moving Average - Nur Khoerudin; Syafira Putri Ramadhani; Mozes Hasian Veltin Sinaga; Dwi Mustika Kusumawardani (JURIKOM (Jurnal Riset Komputer), 2023)
The COVID-19 pandemic has resulted in paralysis of many sectors, such as the economic and education sectors. This has the effect of decreasing turnover felt by school shoe entrepreneurs by around 60 to 70 percent. The occurrence of the COVID-19 pandemic not only caused a decrease in turnover, but also caused a change in people's habits who switched from buying conventional shoes to buying habits through e-commerce stores. In the Purwokerto area, Central Java, there is a Surfskate shop which is a shoe seller. Based on the problem described by the store, shoe sales during the pandemic have decreased. Therefore, school shoe entrepreneurs make changes to their sales strategies such as collaborating with business actors in the surrounding environment and selling through e-commerce such as Instagram, Shopee, Tokopedia, and others. Based on the data obtained, the store experienced an increase in the year before the pandemic and experienced a drastic decline during the COVID-19 pandemic. This study uses the Weight Moving Average (WMA) method, which is a form of improvement from the Simple Moving Average (SMA) method. Gives the greatest weight to new data over older data because the most recent data is considered more relevant to change. Because the data observed from before the pandemic, namely in 2020 with monthly sales reaching 80% and sales of up to 80 units. Then in 2021, during the pandemic, sales fell by 20% / month with sales reaching 20 units.